CLIL teachers' reflections and attitudes: surviving at the deep end - Lazarevic, Nina (International journal of bilingual education and bilingualism, 2022)
The present study is a mixed methods approach that explores subject teachers' views on teaching sciences in English in a context where English is a foreign language, as well as how different teaching philosophies and school atmosphere may influence their work in bilingual science classes. The study was conducted with high school teachers from two schools in Niš, Serbia, that have been involved in a nation-wide project of teaching science subjects in English, within a framework that is conceptualized as CLIL. The data gathered from questionnaires, a focus-group interview, and informal interviews and observations with the subject teachers show that there are several challenges that teachers meet: regarding the legal requirements, organization of CLIL instruction, teachers' language proficiency, material usage and development, and teacher development and support.